2004
DOI: 10.1002/ajim.20094
|View full text |Cite
|
Sign up to set email alerts
|

Physical workload, ergonomic problems, and incidence of low back injury: A 7.5‐year prospective study of San Francisco transit operators

Abstract: TitlePhysical workload, ergonomic problems, and incidence of low back injury: A 7. Physical workload, ergonomic problems, and incidence of low back injury: A 7.5-year prospective study of San Francisco transit operatorsThe etiologic role of biomechanical factors for low back injury (LBI) needs to be confirmed in prospective studies that control for psychosocial factors. Methods: Complete baseline information on 1,233 vehicle operators was gathered during medical examinations and by questionnaire. First LBI dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 45 publications
3
54
0
4
Order By: Relevance
“…The occurrence of new episodes of LBP was measured by the use of questionnaires [22, 24, 25, 27, 28, 31-34, 36, 38, 39, 42, 49, 53-56], interviews [24,41,49] or reports by care providers [50][51][52]57]. Sick leave was derived from questionnaires [25,26,28,29,33,37,38,43,45,47], company registers [23,26,35,40] and social insurance administrations [30,40,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The occurrence of new episodes of LBP was measured by the use of questionnaires [22, 24, 25, 27, 28, 31-34, 36, 38, 39, 42, 49, 53-56], interviews [24,41,49] or reports by care providers [50][51][52]57]. Sick leave was derived from questionnaires [25,26,28,29,33,37,38,43,45,47], company registers [23,26,35,40] and social insurance administrations [30,40,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…standing, awkward positions such as flexed-twisted-rotated), magnitudes of work and non-work-related physical loadings (light, moderate, heavy), sports and physical exercise. The measurement of the outcome (dependent) variable varied between the occurrence of new episodes of LBP [22-24, 27, 31, 32, 34, 36, 39, 41, 44, 46, 50, 52, 54, 57], sick leave due to LBP [23,26,29,30,35,40,43,48] or a combination of both [25, 28, 33, 36, 38, 42, 44-46, 49, 51, 53, 55]. Twentyeight studies applied (self-administered) questionnaires in the screening of exposures [22-24, 26-33, 36, 37, 39, 40, 42-45, 47-49, 52-57].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review that analyzed 19 studies on psychosocial workplace factors and neck-shoulder symptoms concluded that "this relationship is neither very strong nor very specific" (6, p 290). The two reviews criticized that many studies have not sufficiently controlled for exposure to high physical workload and ergonomic problems (7,8). Finally, it is notable, that many studies defined psychosocial working conditions based on the demand-control (job strain) model (9) or its expansion, the demand-control-support model (10), and that there is a lack of research on alternative theoretical models of psychosocial workplace stressors.…”
mentioning
confidence: 99%